Mekanisme Sistem Pembelajaran Tatap Muka Terbatas Di SMP Negeri 4 Sungai Raya Pasca Pandemi Covid-19 - Iwan Ramadhan (Departement of Mathematics Education, 2023)
This study aims to find out the mechanism for implementing limited face-to-face learning after courageous learning and changes in policies implemented at SMP Negeri 4 Sungai Raya. The findings of the problem at SMP Negeri 4 Sungai Raya in the limited face-to-face learning mechanism are in the form of changes in students' behavior and interest in learning as well as new policies that must be implemented by schools and all school members must adjust or adapt from the policies governing the implementation of limited face-to-face learning. However, there are efforts by schools to adapt policies that are in accordance with the guidelines for implementing learning during the Covid-19 period. The research method used includes descriptive qualitative with observation, interview and documentation techniques. The results of research on the mechanism of the face-to-face learning process have been considered with the condition that it is carried out with all the readiness and preparation of all school members and efforts to overcome changes in students after face-to-face learning through learning device strategies whose implementation is limited to time and number of students.